Hubungan Keterlibatan Ayah dengan Bullying Victimization pada Mahasiswa Farmasi di Sumatera Barat - Diva Ingriani; Maya Yasmin (Pusat riset dan Inovasi Nasional, 2025)
This study aims to examine the relationship between paternal involvement and bullying victimization in Pharmacy students in West Sumatra. Using a quantitative approach, this study involved 320 respondents selected from various Pharmacy colleges in the region. The research instrument was independently developed by the researcher, with the paternal involvement scale compiled based on Lamb's (2010) theory which includes the dimensions of direct involvement, emotional availability, and paternal responsibility. Meanwhile, the scale of bullying victimization refers to the theory of Smith et al. (1999), which includes forms of physical, verbal, social, and cyber victimization. Data analysis was conducted using the Pearson correlation technique, which showed a significant negative association between paternal involvement and bullying victimization (r = -0.728; p = 0.000). These findings indicate that the higher the level of father's involvement in a child's life, the lower the likelihood of the child experiencing bullying victimization. On the other hand, low involvement of fathers can increase the risk of students becoming victims of bullying. The results of this study make an important contribution to understanding the role of fathers as a protective factor against victimization behavior, as well as being the basis for the development of family interventions in the context of higher education. This research also opens up space for further studies on family dynamics and student mental health.